Quebec, Canada, and the Glorious Revolution - Graham, John (Les Cahiers de droit, 1996)
The theory of secession in the United States, as acknowleged by New England during the War of 1812 and by the South during the American Civil War, is traced to authentic historical roots, and freshly reexpounded so as to permit renewed consideration of the wisdom of James Buchanan and the error of Abraham Lincoln in 1860 and 1861. The British North America Act of 1867 (Constitution Act of 1867) is then viewed against Sir John Macdonald's misinterpretation of the American Civil War. Events leading to the present constitutional impasse between Quebec and Canada are reexamined, so as to reveal the underlying cause. The author expounds the principle of the Glorious Revolution, as explained by Sir William Blackstone, and shows why, in light of the constitutional custom giving legitimacy to the reign of William and Mary, and the present constitutional order of Canada under Elizabeth II, a reference to the Supreme Court cannot resolve the crisis now erupting in Quebec. The resolution of this crisis can only be accomplished by statesmanship, buttressed by patriotism and courage.